EFEK INFUSA DAGING BUAH TERUNG UNGU TERHADAP KADAR GLUKOSA DARAH TIKUS WISTAR JANTAN YANG DIBEBANI GLUKOSA - ., Alfian Firdaus (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
BackgroundDiabetes melitus is a chronical disease signed by highblood glucose level. Eggplant (Solanum melongena Linn.) is tropical plant,which phytochemicals of its fruit from earlier study had potential effect ashypoglicaemic agents.ObjectiveThe aim of the study was to know the effect of eggplants fruitinfusion on blood glucose level of white rats loaded by glucose comparedwith metformin.MethodThis study was an experiment study with controlled time-seriesdesign used glucose tolerance method. The experiment study used 25male wistar rats which were devided into 5 groups, they were negativecontrol group (aquadest), positive control group (metformin), dose I (5,25g/kgBW) group, dose II (10,5 g/kgBW) group, and dose III (21g/kgBW)groups. First, rats fasted for 18-20 hours, then fasting blood glucose levelwas examined, the next step, rats got 2 times of per-oral administrations,each administration had 30 minutes of time interval. After that, bloodglucose level was observed using Easy Touch glucometer in 0, 15, 30,60, 120 minutes after the second administration. The data was analizedbased on the broad of AUC0-120 with One Way Anova test and Post-HocLSD test.ResultBased on data analysis, there were significant differences ofAUC0-120 between negative control group with positive control group andthree doses group of eggplant fruit (p<0,001), and also between positivecontrol group with dose III group (p=0,036).ConclusionAll doses of eggplant fruit infusion could lower rats bloodglucose level. Dose I (5,25 g/kgBW) and dose II (10,5 g/kgBW) were aseffective as metformin (63 mg/kgBW), whereas dose III (21 g/kgBW) wasless effective than metformin in lowering blood glucose level of rats loadedby glucose.Keywords: Solanum melongena, glucose, hypoglicaemic.1. Medical Study Program, Faculty of Medicine, Tanjungpura